Studies of The Structure of Cytochrome P450 4A1 - Fan, MingQi (2002)
Cytochrome P450 4A1 (CYP4A1) is involved in omega-hydroxylation of fatty acids and eicosanoids. The resulting metabolites may have physiological activities such as regulation of blood pressure. In order to identify structural determinants of substrate binding, site-directed mutagenesis was used. According to a model of CYP4A1, the residues K93, R87 and N116 were predicted to respond to substrate binding. To test the hypothesis, we designed a series of mutants, K93E, R87E, R87E/K93E, R87W/K93E, N116E and N116E/K93E, which would change the substrate specificity of CYP4A1 from a fatty acid to a fatty amine omega-hydroxylase. To reconstitute CYP4A1 activity in vitro, cytochrome b5 and cytochrome P450 reductase were expressed in E.coli and purified. Recombinant CYP4A1 and mutants were expressed in E.coli with an OmpA signal peptide. The conditions of expression were optimised; the enzyme was purified by Ni2+-chelate affinity chromatography. Under optimal conditions, the expression level of CYP4A1 was approximately 60-100nmol/l; mutants were expressed at various levels. The purified enzymes were used in a spectral substrate-binding assay. The K93E mutation did not induce a major change in the substrate specificity from fatty acid to amine; however, K93E showed weak binding to dodecyltrimethylammonium bromide and the Ks (Spectral dissociation constant) value for binding lauric acid increased about three times. R87E mutants had low affinity for lauric acid, but did not show increased affinity for dodecyltrimethylammonium bromide. N116E is similar to wild type CYP4A1 in substrate affinity and specificity. N116/K93E could not be examined owing to the low expression level. These results suggest that K93 is not the principle residue for substrate binding but could be involved in transient contact with substrate; that R87 is crucial for keeping the substrate binding but might not directly contribute to binding of substrate and that N116 does not contribute directly to substrate contact. The residues, H141, R142, R143 and F149, which are located in the conserved Chelix in CYP4A1, were also investigated. We hypothesised that H141 and F149 bind to conserved residues in the I-helix. R142 and R143 may be involved in contacts with electron donors of CYP. Seven mutants including H141R, H141F, H141L, R142A, R143A, F149I and F149Y were constructed. All mutants were expressed and purified as for CYP4A1. R142A was expressed in low level and not further purified. F149I yielded proteins of the expected size, but these proteins did not support a 450nm peak in a reduced CO-difference spectrum, demonstrating an improperly folded enzyme. The enzyme activity of other mutants for lauric acid metabolism is variable; preliminary data showed that the H141L, H141F, R143A and F149Y had very poor enzyme activity, whereas the H141R retained enzyme activity. The results suggest that certain C-helix: I-helix contacts are not required for correct folding of the haem-environment, but are required for function of the P450 enzyme.